PENINGKATAN LITERASI INDONESIA MELALUI BUKU ELEKTRONIK - Anggraeni Dian Permatasari; Khofifa Najma Iftitah; Ence Oos Mukhamad Anwas; Yuni Sugiarti (Balai Besar Guru Penggerak Jawa Timur, 2022)
Various surveys show that the reading literacy of students in Indonesia is still relatively low. One of the contributing factors is the lack of reading books. This research was conducted using a literature review method to analyze the advantages of electronic books in an effort to improve literacy in Indonesia. This study focuses on aspects of: (1) student literacy in Indonesia; (2) the familiarity of generation Z students to electronic-based reading materials; (3) definition, content, and advantages of e-books; and (4) infrastructure and utilization of electronic books. The results of the study show that electronic books can be used to encourage the improvement of reading literacy and digital literacy in Indonesia, especially for Generation Z. One of the supporting factors is the familiarity factor of Generation Z towards electronic-based reading materials. In addition, e-books also have many advantages, including being more attractive, easier to distribute, accessible anywhere, and easier to reproduce or duplicate. The use of electronic books as a means of increasing literacy in Indonesia is also supported by the government in preparing or developing digital reading materials and equitable internet access throughout Indonesia. AbstrakBerbagai survei menunjukkan bahwa literasi membaca siswa di Indonesia masih relatif rendah. Salah satu faktor penyebabnya adalah kurangnya buku bacaan. Penelitian ini dilakukan dengan metode kajian literatur untuk menganalisis keunggulan buku elektronik dalam upaya meningkatkan literasi di Indonesia. Kajian ini difokuskan pada aspek: (1) literasi siswa di Indonesia; (2) familiarity siswa generasi Z terhadap bahan bacaan berbasis elektronik; (3) definisi, konten, dan keunggulan buku elektronik; dan (4) infrastruktur dan pemanfaatan buku elektronik. Hasil kajian menunjukkan bahwa buku elektronik dapat dimanfaatkan untuk mendorong peningkatan literasi membaca dan literasi digital di Indonesia, khususnya untuk generasi Z. Salah satu faktor pendukungnya adalah faktor familiarity generasi Z terhadap bahan bacaan berbasis elektronik. Selain itu, buku elektronik juga memiliki banyak keunggulan di antaranya adalah lebih menarik, lebih mudah didistribusikan, dapat diakses di mana saja, dan lebih mudah diperbanyak atau digandakan. Pemanfaatan buku elektronik sebagai sarana peningkatan literasi di Indonesia juga didukung pemerintah dalam menyiapkan atau mengembangkan bahan bacaan digital dan pemerataan akses internet ke seluruh wilayah Indonesia.